2020
DOI: 10.1136/bmjsem-2019-000681
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical exercise intervention and PPARγ genetic polymorphisms on cardio-metabolic parameters among a Chinese youth population

Abstract: ObjectivePhysical inactivity inChinese youth students particularly in senior high schools, who participate inthe National Higher Education Entrance Examination (NCEE) is very common. Inorder to explore the beneficial effects from physical exercise and education afterNCEE, we performed a Physicalexercise Intervention Program in the Youth (PiPy) to evaluate the interaction with PPARγ genetic variants on cardiovascular and metabolicparameters.MethodsA total of 772 freshmen (males 610/females162) from high schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Type 2 diabetes (T2DM) is one of the most common metabolic disorders worldwide, which is caused by a combination of two main factors: defective insulin secretion by pancreatic beta cells and the inability of insulin-sensitive tissues to respond appropriately to insulin (1). According to the International Diabetes Federation (IDF), 9.3% (463 million) of adults worldwide had diabetes in 2019, and this figure is expected to increase to 10.2% (578 million) by 2030 to increase to 10.9 percent (700 million) by 2045 (2). The prevalence of T2DM among adults and young people has caused great concern, and people with T2DM in youth often have a more aggressive clinical course than people with T2 diabetes in adulthood (3).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes (T2DM) is one of the most common metabolic disorders worldwide, which is caused by a combination of two main factors: defective insulin secretion by pancreatic beta cells and the inability of insulin-sensitive tissues to respond appropriately to insulin (1). According to the International Diabetes Federation (IDF), 9.3% (463 million) of adults worldwide had diabetes in 2019, and this figure is expected to increase to 10.2% (578 million) by 2030 to increase to 10.9 percent (700 million) by 2045 (2). The prevalence of T2DM among adults and young people has caused great concern, and people with T2DM in youth often have a more aggressive clinical course than people with T2 diabetes in adulthood (3).…”
Section: Introductionmentioning
confidence: 99%
“…They found that young Polish women with CC PPARG rs1801282 genotype had a better response for body fat mass variables compared to G allele carriers after a 12-week training program ( 77 ). However, data on this previously debated matter is scarce in the pediatric population and has been so far limited to adolescents, in whom a physical exercise intervention might imply a better compliance as opposed to younger ages ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T2DM is increasing day by day due to the mechanization of living standards, decreased PE, and unhealthy diets. In 2019, 463 million adults worldwide, which accounts for 9.3% of the population, suffered from T2DM, and this number is expected to rise to 578 million (10.2%) by 2030 and 700 million (10.9%) by 2045 4 . Understanding some of the cellular mechanisms underlying this disorder can be helpful in developing appropriate treatment strategies.…”
Section: Introductionmentioning
confidence: 99%